2011
DOI: 10.1080/14786419.2010.482936
|View full text |Cite
|
Sign up to set email alerts
|

Comparative volatile oil composition of fourOcimumspecies from northern India

Abstract: The hydrodistilled essential oils of Ocimum basilicum L. cvs. 'Vikarsudha' and 'CIM-Soumya', Ocimum sanctum L. cvs. 'Green' (CIM-Ayu) and 'Purple', Ocimum gratissimum L. and Ocimum kilimandscharicum Guerke have been studied by capillary gas chromatography (GC) and gas chromatography-mass spectrometry (GC-MS). Phenylpropanoids (65.2-77.6%) constituted the major proportion of the essential oil compositions of O. sanctum, O. basilicum and O. gratissimum, whilst oxygenated monoterpenes (72.7%) constituted the majo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(37 citation statements)
references
References 13 publications
1
32
0
Order By: Relevance
“…Some of the main chemical constituents of Tulsi are: Oleanolic acid, ursolic acid, rosmarinic acid, eugenol, carvacrol, linalool, β-caryophyllene (about 8%), β-elemene (11.0%), and germacrene D (about 2%) [24]. Our results revealed a significant increase in plaque pH after 5 minutes and 30 minutes and a significant increase in calcium and phosphate concentration after chewing tulsi leaves.…”
Section: Discussionsupporting
confidence: 53%
“…Some of the main chemical constituents of Tulsi are: Oleanolic acid, ursolic acid, rosmarinic acid, eugenol, carvacrol, linalool, β-caryophyllene (about 8%), β-elemene (11.0%), and germacrene D (about 2%) [24]. Our results revealed a significant increase in plaque pH after 5 minutes and 30 minutes and a significant increase in calcium and phosphate concentration after chewing tulsi leaves.…”
Section: Discussionsupporting
confidence: 53%
“…[3] The two main morphotypes cultivated in India and Nepal are green-leaved (Sri or Lakshmi Tulsi) and purple-leaved (Krishna tulasi). [4] Ocimum basilicum L. Cvs. Vikarsudha and CIM-Soumya, OS L. Cvs.…”
Section: T Ulsi or Tulasi Or Vaishnavi (Ocimum Tenuiflorummentioning
confidence: 99%
“…EO from Ocimum kilimandscharicum mainly contains monoterpenoids (95.8%), represented by camphor (64.9%), limonene (8.7%), camphene (6. 4%) and (E)-β-ocimene (3.0%), [4] O. basilicum contains methyl chavicol (87.0%) and{(Z)-and (E)-methyl cinnamate (69.1%). [15] EO yield and quality of methyl eugenol rich sacred/holy basil (OT L.f.; Lamiaceae) (E)-cinnamyl acetate, eugenol and beta-elemene constituents of the oil.…”
Section: Medicinal Usesmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the main chemical constituents of tulsi leaves are: oleanolic acid (Figure 66), ursolic acid (Figure 67), rosmarinic acid ( Figure 68), eugenol ( Figure 69), carvacrol, linalool, β-caryophyllene (about 8%), [89] β-elemene (c.11.0%), and germacrene D (about 2%). [90] A variety of invitro studies and animal studies has indicated some potential pharmacological properties of Ocimum tenuiflorum or its extracts. Recent studies suggest tulsi may be a COX-2 inhibitor, like many modern painkillers, due to its high concentration of eugenol.…”
Section: Ginkgo Biloba (Maidenhair Tree)mentioning
confidence: 99%